Gender Differences in Audience Engagement and Interpretation of Global Media Content - Anna Maria Kontolatou (Journalism and Media)
This study investigates the relationship between gender and global media consumption habits, platform preferences, and engagement types. Prior research suggests that gender significantly influences media preferences, with men being traditionally engaged with news, action-oriented content, and competitive media, and women with entertainment, lifestyle, and social media-driven content. The current primary quantitative research is based on a questionnaire that was distributed online and answered by 292 respondents, equally distributed between men and women. The research findings showed that men are more likely to consume news, video games, and discussion-based media. On the other hand, women showed higher engagement with entertainment content, music, and listening-based media. Pearson’s correlation analysis, conducted using SPSS (v23), further confirmed these gendered preferences. Despite the persistence of traditional gendered media patterns, this research also identified the areas in which digital platforms seem to facilitate more balanced engagement across the two genders.